Effect of different weather parameters on blast disease severity of pearl millet under North Gujarat conditions - Chaudhary, D H; Jaiman, R S; Chaudhary, Mahesh (Indian Journal of Plant Protection, 2024)
A study was conducted to find out the effect of weather factors on the progress of pearl millet blast disease during Kharif seasons 2018 and 2019. The first leaf blast intensity was recorded from the initiation of disease fifteen days after sowing and gradually increased up to harvesting on all different dates of sowing in both crop seasons. All the weather parameters (max temp. (-0.358), min temp. (-0.795), morning relative humidity (-0.524), evening relative humidity (-0.327), rainfall (-0.543), and rainy days (-0.535)) exhibiteda negative correlation in the D1 date of sowing. While in D2, D3, and D4, maximum temperature (0.314), (0.506), and (0.608) showed positive relationships, other weather parameters (min. temperature (-0.840), (-0.510), and (-0.917), morning relative humidity (-0.563), (-0.615), and (-0.735), evening relative humidity (-0.606), (-0.700), and (-0.775), rain fall (-0.659), (-0.439), and (-0.392), and rainy days (-0.526), (-0.514), and (-0.594) exhibited negative relationships with blast disease intensity, respectively, during 2018. In 2019, D1, D2, and D3 morning relative humidity (0.790), (0.683) and (0.253), evening relative humidity (0.747), (0.595) and (0.302), rain fall in mm (0.445), (0.189) and (0.071), and rainy days (0.697), (0.535) and (0.413) showed a positive relationship, while maximum temperature (-0.774), (-0.643) and (-0.404) and minimum temperature (-0.662), (-0.711) and (-0.602) exhibited a negative relationship with diseaseintensity. In D4, the minimum temperature (-0.674), morning relative humidity (-0.617), evening relative humidity (-0.480), rain fall (-0.048), and rainy days (-0.096) showed negative relationships, while only the maximum temperature (0.289) exhibited a positive relationship with disease intensity.